Khalid Yusoff auditorium complex - Baharudin, Nabilah (Faculty of Medicine, 2022)
Emeritus Professor Dato’ Dr. Khalid Yusoff is a name that can never be separated from the Faculty of Medicine UiTM. Although he was no longer with the faculty, he remains as the key figure in building the reputation of the faculty and the longest serving Dean. His contribution towards the faculty during his tenure were countless and can never be challenged. Some of his major contributions proposing and establishing the UiTM Teaching Hospital, which has been in operation since April 2021 and has been renamed as Hospital Al-Sultan Abdullah by His Majesty the Yang di-Pertuan Agong Al-Sultan Abdullah on 23 July 2022. He was also responsible in establishing medical campuses in Selayang and Sungai Buloh which includes the establishment of Sungai Buloh Clinical Training Centre (CTC), which is today known as the UiTM Medical Specialist (PPUiTM), to serve as a training facility for medical students and lecturers